The political implications of Kant's theory of knowledge : rethinking progress - Lahat, Golan Moshe (UK: Palgrave Macmillan, 2013)
"Immanuel Kant has long been considered one of the leading exponents of the theory of knowledge with his philosophical writings inspiring generations of political theorists, underpinning many notions and ideas on the concept of progress. Based on and innovative reading of Kant's theory of knowledge, this book challenges contemporary critiques of the concept of progress from post-Marxist, post-Modern and or existentialist approaches which dismiss progress as an anachronistic and deceptive concept that has formed the basis of many of modernity's abominations. Instead this book reveals Kant's unique synthetic theory of knowledge, arguing that the idea of progress should be thought of as a crucial political idea in matters of political management at the outset of the 21st century"--
Machine generated contents note: -- Preface -- Acknowledgments -- Introduction - On the Concept of Progress -- PART I: WHAT CAN WE KNOW? -- 1. Kant's Theory of Knowledge -- 2. A Proposal for Three Boundaries of Cognition -- 3. The Regulative Idea -- PART II: WHAT OUGHT WE DO? -- 4. The Primacy of Practical Reason -- 5. Setting the Moral Principle as Categorical Imperative -- 6. The Essence of the Categorical Imperative -- PART III: WHAT CAN WE HOPE FOR? -- 7. The Political According to Kant -- 8. Regulative Politics -- Conclusion: On the Possibility of Regulative Progress -- Author's Notes -- Notes -- Bibliography -- Index.
Includes bibliographical references and index
Keywords: Kant, Immanuel, -- 1724-1804 -- Political and social views; Kant, Immanuel, -- Political and social views; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Political Ideologies / General